The Wali-Songo and (Western) Historiography: A Critical Review of a Methodological Achievement - Sakhok, Jazilus; Musadad, Asep Nahrul (Journal of Al-Tamaddun, 2024)
Since the early 19th century, Western academics, particularly Dutch philologists, have been leading the way in modern research on Javanese history and literature. This scholarship has significantly influenced the narrative of Indonesian history in various aspects. However, despite its noteworthy legacy, there have been some challenges to the emic and native perspectives. This study aims to address this issue by examining the wali-songo (the Javanese nine saints) narrative in Western historiography. The study will critically review the contribution of Western scholars in explaining the narrative of wali-songo, primarily in terms of methodology. It will also highlight the legacy and impact of this scholarship on the intellectual history of Indonesia, specifically in the context of the wali-songo narrative. Ultimately, this paper seeks to bring about a nuanced understanding of the “historiography of wali-songo” in light of existing scholarship on this topic.